Assessing structural change in the Maltese economy via the application of a hypothetical extraction analysis - Ian P. Cassar (Central Bank of Malta, 2017)
This paper assesses the extent of change in the production structure of the Maltese Economy on the basis of three symmetric input-output tables via the application of hypothetical extraction analysis.
Keywords: C63; C67; D57; 330